Book publishing textbooks for higher education: traditions and innovations - Natalia V. Priadilnikova; Anna A. Gnutova; Sergej A. Nechitaylo (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article deals with the combination of traditional and innovative pedagogical technologies in educational publishing for higher education, capable to implement the textbook model of a new generation of two-tier system of education and ensure that the challenges facing the modern higher education. Schematically presented the content and structure of traditional and innovative model of university books, basic typological features of academic repertoire strategies and typological features an innovative model of academic publication of the strategy repertoire. Published results of a survey on the attitude to cooperation with educational Text edition among students of 1-3 courses of full-time training.